The impacts of using Twitter by rulling party toward youth / Muhammad Amirudin Ali Sabri and Safwan Ab Rahman - Ali Sabri, Muhammad Amirudin; Ab Rahman, Safwan (2012)
Social networking sites such as web-based service that allows individuals to construct public or semi-public profile within the area bounded system, articulate a list of other users with whom they share a connection and to view and cross list their connections and made others in the system. Social networking sites (SNS), like MySpace, Flickr, Twitter and Facebook which attracted significant media attention over the last few years. The emergence of new media in the country brought the major change in politics landscape of those countries. For example we can see that this situation during the Egyptian parliamentary elections, in Egypt which is Hosni Mubarak, has lost during parliamentary elections. Hosni Mubarak collapsed caused by rise of young people to be free of cruel rule which full of fraud, corruption and repression against the people. One of the factors lost Hosni Mubarak in elections is the emergence of new media namely internet social networking site which is important component in the Egyptian revolution. But different in Malaysia, in 2008 which the ruling Barisan Nasional failed to get control of five state governments and are not able to get two-third majority in parliament. These occur because of the emergence and development of information and communication technology (ICT) has changed the role of media in democracy. This fall occurred because of the ruling party control in the use of the media is too biased in the dissemination of information causes people more confidence to the emergence of new media such as Twitter, and phone Facebook, Blog, Phone cell. It because this system provides information more quickly, accurately and not controlled by any power.So the question is whether the emergence of social network can still became the main weapon of media for the government to attract the young voters in next general election in Malaysia? Is there the government was able to regain the five states that are administered by the opposition party by using social network?